2022
DOI: 10.1101/2022.06.06.22275103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elite neutralizers of human cytomegalovirus are characterized by high magnitude plasma IgG responses against multiple glycoprotein complexes

Abstract: Background. Human cytomegalovirus (HCMV) is the most common infectious complication of organ transplantation and cause of birth defects worldwide. There are limited therapeutic options and no licensed vaccine to prevent HCMV infection or disease. To inform development of HCMV antibody-based interventions, a previous study identified individuals with potent and broad plasma HCMV-neutralizing activity, termed elite neutralizers (EN), from a cohort of HCMV-seropositive (SP) blood donors. Yet, the specificities an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Future HCMV vaccine design should consider several perspectives. We recently demonstrated that elite neutralizers of HCMV have potent neutralizing antibody responses that target multiple glycoprotein specificities 69 , including pentameric and trimeric glycoprotein complexes on the HCMV virion surface. However, there was no difference in gB-specific binding breadth comparing the HCMV-seropositive elite neutralizers to non-elite neutralizing individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Future HCMV vaccine design should consider several perspectives. We recently demonstrated that elite neutralizers of HCMV have potent neutralizing antibody responses that target multiple glycoprotein specificities 69 , including pentameric and trimeric glycoprotein complexes on the HCMV virion surface. However, there was no difference in gB-specific binding breadth comparing the HCMV-seropositive elite neutralizers to non-elite neutralizing individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer (NK) cell-mediated ADCC. NK cell degranulation was quantified by cell-surface expression of CD107a as previously described (47). MRC-5 fibroblasts (target cells; ATCC) were infected with HCMV strain AD169r (a AD169 derivative with repaired UL128-131 expression named BadrUL131-Y4-GFP ( 48)) at an MOI of 1.0 or mock-infected.…”
Section: Methodsmentioning
confidence: 99%